King John in the “Vormärz”: Worrying Politics and Pathos - Robert Gillett (Multicultural Shakespeare, 2019)
This article picks up on a tendency of recent criticism to look to Shakespeare for insights into contemporary politics, and extends it backwards to the period of German history known as the “Vormärz”―the period between 1815 and 1848. It establishes parallels between that period and the current debates about Brexit, and shows how equivalent issues are reflected in the accounts of King John given by three leading German critics of the “Vormärz” period―which also successively demonstrate the deleterious rise of German nationalism. These issues include: the weaknesses, mistakes and crimes of the powerful, and their effect both on the nation directly afflicted with them, and on others; the issue of national sovereignty and its relationship to the fellowship of nations; the struggle against arguably alien ways of thinking; the dividing line between necessary compromise and rank betrayal; the dilemma of choice; and the poisoned chalice of democratic freedom. And the parallels they establish between Shakespeare, the “Vormärz” and us are as instructive as they are unsettling.